2003
DOI: 10.1167/iovs.02-1215
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar Diameter and Microvascular Factors as Independent Predictors of Mortality from Malignant Melanoma of the Choroid and Ciliary Body

Abstract: In this population-based data set, MLN and microvascular loops and networks were unrelated, independent predictors of survival. MLN and MVD were found to be partially interrelated. Multivariate models that included MVD in addition to MLN fitted better with observed melanoma-specific survival than models that excluded MVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
2
13
0
1
Order By: Relevance
“…2004). We have previously confirmed that MLN is a predictor of survival after enucleation in primary uveal melanoma (Al Jamal et al. 2003).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…2004). We have previously confirmed that MLN is a predictor of survival after enucleation in primary uveal melanoma (Al Jamal et al. 2003).…”
Section: Discussionsupporting
confidence: 58%
“…1998; Moshari & McLean 2001). We have proved earlier that MLN is an independent predictor of survival in primary choroidal and ciliary body melanomas (Al Jamal et al. 2003).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Emdogain also acts on genes related to the immune system (Apte et al , 2001; All‐Ericsson et al , 2002; Al‐Jamal et al , 2003). ICA1 is a 69‐kDa peptide autoantigen associated with insulin‐dependent diabetes mellitus (Pietropaolo et al , 1993; Gaedigk et al , 1994, 1996; Winer et al , 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Poor prognosis has been reported with a number of tumour characteristics including anterior location of melanoma (Seddon et al 1983; Kroll et al 1998; Isager et al 2004), large size tumours mainly with large basal tumour diameter (Shammas & Blodi 1977; Seregard & Kocks 1995; Coleman et al 1996; Damato et al 1996; Isager et al 2006; McLean et al 2004), epitheloid cell type (Seregard & Kock 1995; Mäkitie et al 1999; Singh et al 2001; Al‐Jamal & Kivelä 2006), high number of tumour infiltrating lymphocytes (McLean et al 2004; Niederkorn & Wang 2005) and microvascular channels (Rummelt et al 1995; Mäkitie et al 1999; Al‐Jamal et al 2003; Kivelä et al 2004). With Kaplan‐Meier and Cox regression analyses, it has been shown that the 10‐year melanoma‐specific mortality rate increases with higher numbers of tumour‐infiltrating CD68‐positive macrophages (Mäkitie et al 2001).…”
Section: Introductionmentioning
confidence: 99%